2019
DOI: 10.1007/s12035-019-01781-9
|View full text |Cite
|
Sign up to set email alerts
|

The Homeodomain Transcription Factors Vax1 and Six6 Are Required for SCN Development and Function

Abstract: The brain's primary circadian pacemaker, the suprachiasmatic nucleus (SCN), is required to translate day-length and circadian rhythms into neuronal, hormonal, and behavioral rhythms. Here, we identify the homeodomain transcription factor Ventral anterior homeobox 1 (Vax1) as required for SCN development, vasoactive intestinal peptide expression, and SCN output. Previous work has shown that VAX1 is required for gonadotropin-releasing hormone (GnRH/LHRH) neuron development, a neuronal population controlling repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 85 publications
2
15
0
Order By: Relevance
“…Six3 and Vax1 are important for eye and brain development, whereas their roles in the post‐developmental brain are far less studied. We confirmed that expression of both Six3 and Vax1 is maintained in the adult hypothalamus, and both genes are highly expressed in the SCN (Pandolfi, Breuer, et al, 2019; VanDunk et al., 2011). We recently showed that conditional deletion of Vax1 in the developing SCN impacts circadian rhythms of wheel‐running activity (Pandolfi, Breuer, et al, 2019).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Six3 and Vax1 are important for eye and brain development, whereas their roles in the post‐developmental brain are far less studied. We confirmed that expression of both Six3 and Vax1 is maintained in the adult hypothalamus, and both genes are highly expressed in the SCN (Pandolfi, Breuer, et al, 2019; VanDunk et al., 2011). We recently showed that conditional deletion of Vax1 in the developing SCN impacts circadian rhythms of wheel‐running activity (Pandolfi, Breuer, et al, 2019).…”
Section: Discussionsupporting
confidence: 75%
“…in the developing SCN impacts circadian rhythms of wheelrunning activity(Pandolfi, Breuer, et al, 2019). To shed light on TA B L E 5 Circadian parameters in Vax1 syn Analysis of circadian parameters of Vax1 fl/fl and Vax1 syn females on running wheels.…”
mentioning
confidence: 99%
“…Using conditional KO mice (Cre-LoxP system) comes with numerous potential caveats to consider in data interpretation [ 43 , [73] , [74] , [75] , [76] , [77] , [78] ]. We have recently further validated the effectiveness of the Synapsin cre -allele for inducing recombination of the Six3 flox -allele throughout the brain, including the SCN, PVN, and PeVN [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Six6 is required for early eye development, GnRH neuron, and SCN development in vertebrates [ 32 , 33 ]. The suprachiasmatic nucleus (SCN), the brain’s primary circadian pacemaker, is required to translate day-length and circadian rhythms into neuronal, hormonal, and behavioral rhythms [ 34 ]. Migration is a rhythmic behavior.…”
Section: Discussionmentioning
confidence: 99%